Implementasi - Dzaky Hafizh Muttaqien; Andieni Putri Olivia Arifin; Yusuf Baihaqi; Masruchin (ISTAWA, 2025)
Tahfidz Al-Qur’an learning in Islamic educational institutions has predominantly emphasized quantitative memorization outcomes, while the integration of meaning, educational values, and pedagogical orientation derived from the Qur’an remains underdeveloped at the curricular level. This study examines the revitalization of the tahfidz curriculum based on tafsir tarbawi through an analysis of Surah al-Muzzammil and its implications for teaching methods. Employing a qualitative library research approach, data were drawn from the Qur’an, classical and contemporary tafsir works, and scholarly literature on Islamic education and tahfidz pedagogy, and analyzed using qualitative content analysis. The findings reveal that Surah al-Muzzammil contains core educational values (namely spiritual discipline (qiyam al-layl), gradual learning, tartil-based recitation, patience, and consistency) which can be systematically translated into curricular objectives, learning content, and instructional strategies in tahfidz education. The study further identifies a conceptual shift from memorization-oriented instruction toward a meaning (based, reflective, and character) formative tahfidz model grounded in tafsir tarbawi. This research fills a conceptual gap by offering a structured framework for integrating Qur’anic educational interpretation into tahfidz curriculum design, thereby contributing to the development of a more holistic and pedagogically grounded model of Qur’anic learning aligned with the broader aims of Islamic education.